A 2 GSps, 8-Bit Folding and Interpolation ADC with Foreground Calibration in 90 nm CMOS Technology. (26th January 2017) - Zhang, Yi; Meng, Qiao; Zhang, Changchun; Zhang, Ying; Guo, Yufeng; Zhang, Youtao; Li, Xiaopeng; Yang, Lei
Abstract : A single channel 2 GSps, 8-bit folding and interpolation (F&I) analog-to-digital converter (ADC) with foreground calibration in TSMC 90 nm CMOS technology is presented in this paper. The ADC utilizes cascaded folding, which incorporates an interstage sample-and-hold amplifier between the two stages of folding circuits to enhance the quantization time. A master-slave track-and-hold amplifier (THA) with bootstrapped switch is taken as the front-end circuit to improve ADC's performance. The foreground digital assisted calibration has also been employed to correct the error of zero-crossing point caused by the circuit offset, thus improving the linearity of the ADC. Chip area of the whole ADC including pads is 930  μ m × 930  μ m. Postsimulation results demonstrate that, under a single supply of 1.2 volts, the power consumption is 210 mW. For the sampling rate of 2 GSps, the signal to noise and distortion ratio (SNDR) is 45.93 dB for Nyquist input signal.